The wizard of evesham & the murderous marriage eaudiobook - Beaton, M. C. (Agatha Raisin Mystery, 2009)
The fourth volume in the M. C. Beaton mystery series, starring Penelope Keith. The Wizard of Evesham - Agatha is alarmed when her new wizard of a hairdresser seems keen to take on more than just her split ends. She soon discovers that everyone in his salon has a secret and that he practices a very dark magic indeed. The Moment of Truth - Agatha must quickly discover the identity of the prisoner, but James is refusing to help. Has he really ceased to care for her? The Murderous Marriage - After pursuing him for nearly four years, Agatha is finally about to marry James Lacey, the handsome Colonel next door. But there's just one little problem... The Disappearing Trick - With her marriage dreams in tatters, Agatha has the small task of returning the wedding presents, and the slightly larger one of clearing her name of murder.